Simulation Study on CCD Tomography System for Ruby Stone Optical Properties - Syarfa Najihah Raisin; Irneza Ismail; Yasmin Abdul Wahab; Ruzairi Abdul Rahim; Mus'ab Sahrim; Sharma Rao Balakrishnan; Wan Zakiah Wan Ismail; Fatinah Mohd Rahalim; Farah Aina Mohd Jamal; Nurul Arina Hazwani Samsu Zaini; Juliza Jamaludin (MyCT Publishers, 2024)
Non-Indexed Publication